DISTRIBUSI PENDAPATAN PETANI DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA (Income Distribution of Farmers in South Tonsewer Village, Tompaso Barat Sub District, Minahasa Regency) - Febiola L. Manongko; Mex L. Sondakh; Oktavianus Porajouw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The objective of this study is to analyze the income distribution of farmers in South Tonsewer Village. The study was conducted from September to November 2019. The method used in this study was the simple random sampling method. The data used in this study are primary data and secondary data. The research results showed that the income distribution of farmers in South Tonsewer Village was imbalanced with a low Gini index value of 0.33. However, if the income of farmers is only from farming, the Gini index value of 0.36 is included in the moderate inequality.Keywords: Revenue, Distribution, Inequality